Calicovesicostomy for ureteropelvic junction obstruction in a solitary ectopic pelvic kidney - Chavda S.K., M MED, FCS (ECSA), FICS, (The Annals of African Surgery, 2010)
A solitary dysmorphic ectopic kidney is an uncommon congenital abnormality. This anomaly may be associated with ureteropelvic junction obstruction causing hydronephrosis and parenchymal thinning. We report such a case with non-dependent posteriorly placed pelvis in a pelvic kidney and its management. The perioperative results were satisfactory. This seems to be the first such case report of a calicovesicostomy used as a salvage procedure for an ectopic solitary kidney